Restorative Justice for Corruption Cases the Settlement of Corruption Cases: is it Possible? - Rizal Faharuddin; Jefferson Hakim (Universitas Airlangga, 2023)
The Corruption Law of Indonesia regulate the return of the state’s losses suffered by state shall not exclude the criminal acts performed by the perpetrators. In practice, the state’s financial loss due to corruption is less than the cost of enforcing the relevant law. Furthermore, a corruption case requires manpower and lengthy process. Thus, the novel idea of settling minor state financial losses in corruption cases by means of returning the losses is considered more effective when applied with certain conditions. The research method of this study is normative judicial. The data used are primary, secondary and tertiary. This study argues that the concept of restorative justice could be applied to the settlement of corruption cases with minor state finance losses with certain conditions. The restorative justice approach to handling cases of corruption emphasises the restoration of the original state of affairs prior to the corruption, the application of restorative justice includes the stoppage of cases in the examination, investigation, and prosecution stages by considering the interest of the state, society, and other legal interests to be protected, the avoidance of negative stigma and retaliation, as well as society’s response to such as resolution.